Implementation of Free Trade Zone Licensing Services through the Indonesia Batam Online Single Submission (IBOSS) System in Batam City - Balqis, Salsabila; Mashur, Dadang (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Batam City is a Free Trade Zone (FTZ) area or Free Trade Zone and Free Port. Government Regulation Number 41 of 2021 concerning the Implementation of Free Trade Zones and Free Ports regulates licensing service procedures in free trade zone areas integrated with the Indonesia Batam Online Single Submission (IBOSS) system. The change from manual to online creates new problems for licensing services in the Batam City free trade zone area. This research aims to analyze and describe the implementation of free trade zone licensing services through the Indonesia Batam Online Single Submission system in Batam City, as well as identifying obstacles in its implementation. The theory used in this research is Charles O. Jones' policy implementation theory which is seen from 3 indicators, namely, organization, interpretation, and application or application. This research uses descriptive qualitative methods. The results of this research found that the organizations involved in implementing licensing services in free trade zone areas through the IBOSS system are not yet optimal, there are still differences in understanding which often make things difficult for business actors. Meanwhile, from the aspect of interpretation, the Batam Concession Agency is pursuing integration between the IBOSS system and related agencies and systems. Regarding the application/implementation aspect of the IBOSS system in Batam City, the existence of the IBOSS system does provide convenience compared to previously being done offline or face to face, however in its implementation the IBOSS system is not yet optimal in providing services. The inhibiting factors in this research are the problems of perception differentiation between related directorates, system disintegration, the quality of equipment that must be high, and the insufficient quality of information systems.